Penerapan Metode SAW Dalam Pemilihan Penyuluh Agama Islam Teladan di Ulu Rawas - Hamidani, Syafi'ul; Alfiarini, Alfiarini (JATISI, 2024)
The selection of exemplary Islamic religious instructors is an activity that has existed several years ago and there are technical instructions from the Ministry of Religion, but so far it has not used computerization in storing data or calculating selection decisions so it is felt that there is a decision support system that supports the selection of exemplary Islamic religious instructors in the sub-district. Ulu Rawas, this research proposes the application of the Simple Additive Weighting (SAW) Method as a systematic approach in selecting exemplary Islamic religious instructors in Ulu Rawas where 12 instructors are available as alternative data and a number of instructor data. The results of the research obtained alternative 1 with the name Subhan Apriando as the most basic preference with a value of 0.947679021 and can be used as a reference for the decision of an exemplary Islamic religious instructorf.